3D shape measurement using fixed camera and handheld laser scanner - Hirofumi Nakai; Daisuke Iwai; Kosuke Sato (2008 SICE Annual Conference : 20-22 August 2008, 2008)
This paper presents a 3D shape measurement system using a fixed camera and a handheld 1D laser range finder based on Time-of-Flight method. The user of the system only has to sweep the slit light projected from the sensor onto the measured object to obtain its entire shape data. To achieve this, the relative 6DOF of rotation and translation between the sensor and the camera has to be estimated at each frame. We propose to estimate the perspective transformation matrix through matching of the range data and the captured slit light. We built the first prototype system and measured a 3D shape of a simple shaped object.